(untitled) (Global Scientific Review, 2026)
This study analyzes the role of scientific and technological potential as a key driver of regional integration, examining its political, institutional, and normative aspects. The research aims to systematically determine how scientific and technological potential can accelerate regional economic and political cooperation. The arguments presented are based on a mixed-methods approach that includes comparative analysis, indicator-based assessment, and theoretical modeling. Key indicators of scientific and technological potential include R&D expenditures, number of patents, high-tech production output, and the capacity of scientific and academic personnel. A comparison of different regions serves to empirically validate the theoretical model. Regions with high scientific and technological potential exhibit more advanced regional integration, stronger economic cooperation, and faster institutional harmonization. Empirical data confirms a positive correlation between R&D expenditures, the number of patents, and the level of regional cooperation. Additionally, the capacity of scientific and academic personnel enhances the legitimacy and effectiveness of the integration process. Scientific and technological potential can act as a key driver of regional integration, not merely a supporting factor. To achieve this, it is recommended to develop regional innovation clusters, reduce technological inequality, and effectively leverage scientific and technological potential in collaboration with the region’s countries to address global challenges (climate change, pandemics, financial instability). This approach makes it possible to render the regional integration process sustainable and normatively legitimate.